Psychological Impacts of Infertility Among Married Women Attending in a Tertiary Hospital, Dhaka (Anwer Khan Modern Medical College Journal, 2018)
Background: Infertility being a medical problem leads to various psychological problems. The stress of the non-fulfillment of a wish for a child has been associated with emotional sequel such as depression, anger, marital problems among infertile women. The study investigates the psychological impacts of infertility among married women suffering from infertility.Material and Methods: This cross sectional descriptive study was carried out on 112 purposively selected infertile married women in outpatient department of Kormitola General Hospital, Dhaka. The Goldberg Depression questionnaires (GDQ) and Beck Anxiety Inventory (BAI) were administered to 112 married women with infertility. In addition to socio-demographic data, a structured questionnaire was used to collect obstetric information from the participants.Results: The study showed 70 (62.5%) infertile women showed different levels of depression (GDQ scale). Of these, 12 (10.7%) had minor to moderate and 36 (32.1%) had moderate to severe level of depression. According to BAI, 42 (37.5%) responded suffered with anxiety disorders among them 14 (12.5%) had moderate anxiety and 28 (25.0%) potentially concerning levels of anxiety. Infertile women are worst victim of psychological morbidities with increasing age. Study showed that about 54% infertile women of more than 31years of age were suffering from minor to severe depression. Women who were infertile lower than 5 years, had lowest psychological disorders (c2=21.34, P=.001 and c2=8.5, P=.01). About anxiety, women married for more than 11 years were the worst sufferer. Women neglected by their husband had a higher prevalence for psychiatric morbidity (c2=12.22, P=.002). Women suffering from infertility scored significantly higher on all outcome measures of psychopathology. The results of the multiple regression analysis showed that the socio-demographic variables of the women with infertility contributed to the prediction of psychiatric morbidity (GDQ sacle), because of the effects of age, not having at least one child and lack of support from husband. Monthly family income, negligence of husband and violence by in laws family were important predicator for anxiety. Type of family, low level of education, unemployment were not found to be predictors of mental ill health.Conclusion: Infertility is associated with high levels of psychiatric morbidity. Our findings reinforce the need of attention, counseling and others advance psychological interventions for positive impact on outcome during treatment of this group of women.Anwer Khan Modern Medical College Journal Vol. 9, No. 1: Jan 2018, P 10-14